The influence of supralaryngeal settings on phonation - Horga, Damir (2012)
The paper investigates the influence of the supralaryngeal setting on phonation. Twelve female students whose mother tongue is Croatian pronounced the speech material in three conditions: without disturbance of pronunciation, with the closed bite-block (a plate between incisors 1 mm thick) and with the open bite-block (a plate between incisors 10 mm thick). The following variables have been analyzed: the long term average spectrum, the fundamental frequency of vowels and voiced plosives, as well as voice perturbations. The results have shown that changes in supralaryngeal conditions influence the acoustic parameters of voice and that the subjects tune their phonatory mechanisms to the new conditions. This phenomenon is explained by the changes in tension of laryngeal musculature, by the changes in aerodynamic conditions and by the changes in feed-back impedance of the supralaryngeal setting.